Effect of Colocasia Esculenta (L.) Schott (Araceae) ethanol leaf extract on sperm concentration in male Wistar rats (2023)
Colocasia esculenta (L.) Schott (Araceae) is a staple food which supply needed nutrients in Africa and is therefore, employed in ethnomedicine. This study aimed to evaluate the effect of the leaf ethanol extract as well as its partitioned fractions (ethyl acetate, butanol and aqueous) on some male reproductive parameters such as sperm count, motility and morphology as well as the histology of testes in male Wistar rats after 15 days of administration of the extracts/fractions. The ethanol extract showed significant increases of 66 and 213% in sperm concentration at 500 and 1000 mg/kg respectively. This activity was largely retained in the ethylacetate with 200, 213 and 300% in sperm concentration at 50, 100 and 200 mg/kg, respectively and aqueous fractions with 274 and 657% increase at 50 and 100 mg/kg, respectively. Motility and morphology were not significantly altered. The histology of the tests revealed that spermatozoa cells were the positively affected cells.